HUBUNGAN DUKUNGAN SOSAL SUAMI DENGAN PERILAKU PEMBERIAN ASI ESKLUSIF PADA SUKU TOLAKI DI PUSKESMAS KEMARAYA KOTA KENDARI PROVINSI SULAWESI TENGGARA - Farming Farming; Fitriyanti Fitriyanti; Hartati Bahar (Program Studi Gizi FKM UHO, 2023)
Abstrak Air susu ibu (ASI) adalah makanan terbaik bayi pada awal usia kehidupannya. Hal ini tidak hanya karena ASI mengandung cukup zat gizi tetapi juga karena ASI mengandung zat imunologik yang melindungi bayi dari infeksi.Jenis penelitian yang akan dilakukan adalah observasional dengan rancangan cross sectional study. Penelitian ini akan dilakukan di Puskesmas Kemaraya Kota Kendari Provinsi Sulawesi Tenggara. Populasi dalam penelitian ini adalah seluruh suami dari ibu yang mempunyai bayi usia 6-12 bulan yang ber suku tolaki di Puskesmas Kemaraya yang berjumlah 85 orang terhitung pada bulan September sampai November tahun 2018. Teknik pengambilan sampel dalam penelitan ini dilakukan dengan cara purposive Sampling, dengan jumlah sampel 70 orang. Berdasarkan hasil yang di dapatkan dari penelitian ini, berdasarkan hasil Observasional dengan rancangan cross Sectional Study hasil menggunakan analisis Chi Square (X²) pada tingkat kemaknaan 95% menunjukkan bahwa ada hubungan yang signifikan antara Dukungan Informasional dengan perilaku pemberian ASI eksklusif Pada Suku Tolaki di Puskesmas Kemaraya Kota Kendari Provinsi Sulawesi Tenggara Tahun 2018 yang ditandai dengan nilai p = 0,000 < α = 0,05 dengan X2 hitung = 14,069.Kesimpulan dari penelitian menunjukkan bahwa Ada hubungan yang signifikan antara dukungan sosial suami dengan perilaku pemberian ASI eksklusif Pada Suku Tolaki di Puskesmas Kemaraya Kota Kendari Provinsi Sulawesi Tenggara Tahun 2018. Kata kunci: ASI Eklusif, Dukungan Sosial, Suami, Suku Tolaki Abstract Mother's milk (ASI) is the best baby food at the beginning of life. This is not only because breast milk contains enough nutrients but also because breast milk contains immunologic substances that protect infants from infection. The type of research to be conducted is observational with a cross-sectional study design. This research will be conducted at the Kemaraya Community Health Center, Kendari City, Southeast Sulawesi Province. The population in this study were all husbands of mothers who had babies aged 6-12 months who were of the Tolaki ethnic group at the Kemaraya Health Center, totaling 85 people from September to November 2018. The sampling technique in this research was carried out by purposive sampling, with a total a sample of 70 people. Based on the results obtained from this study, based on observational results with a cross sectional study design the results using Chi Square analysis (X²) at a significance level of 95% indicate that there is a significant relationship between Informational Support and exclusive breastfeeding behavior in the Tolaki Tribe at the Kemaraya Health Center, Kendari City, Southeast Sulawesi Province in 2018 which was marked by a value of p = 0.000 <α = 0.05 with X2 count = 14.069. The conclusions from the study showed that there was a relationship between husband's social support and exclusive breastfeeding behavior in the Tolaki tribe at the Kemar aya Kota Health Center Kendari Province of Southeast Sulawesi in 2018.Articles begin with Article Title, Author Name, Author Affiliation, followed by abstracts written with 200-250 words. Especially for Abstracts, the text is written with the left margin of 35 mm and the right margin is 30 mm with a font size of 9 pt and the Book Antiqua font type and the distance between single space lines. Abstracts must be written in Indonesian and English that are good and correct. The Abstract section must contain the core problems and objectives to be achieved, methods, and scientific findings obtained as well as conclusions. Abstracts for each language can only be written in one paragraph in a single column format. Keywords: Exclusive Breastfeeding, Social Support, Husband, Tolaki Tribe